Supervisi Kepala Madrasah dalam Meningkatkan Profesional Guru MTs Al-Mahrusiyah Lirboyo Kota Kediri - Efendi, Are; Moh. Turmudi; Susilo, Suko (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
This study aims to determine the Supervision of Madrasah Heads in Improving Professional Teachers of Mts Al Mahrusiyah Lirboyo Kediri City. To make a professional teacher, a teacher not only improves his competence through his participation in upgrading activities organized by educational institutions, as well as training activities to gain knowledge of learning alone, but other factors that must be considered by the madrasah head is how efforts are made in improving teacher discipline. This research uses a type of field research, with a qualitative approach, the subject of the research consists of the head of the madrassa, staff, and IPAI teachers.The data collection technique is taken from interviews, documentation, and observation. Based on the results of the study, it can be seen that the first implementation of supervision carried out by the head of Madrasah in improving the professional competence of teachers at MTs Al Mahrusiyah through work supervision and the beginning of the year, supervision of teacher administration, supervision of the implementation of learning through observation by directly entering the classroom directly. Second, the implications or results after implementing madrasah head supervision in improving teacher professionalism carried out by the head of MTs Al Mahrusiyah Lirboyo that some teachers in the madrasah already have criteria such as having talent as a teacher, having expertise as a teacher, having a healthy mentality, being able-bodied, having extensive experience and knowledge.